The Elm1 Kinase Functions in a Mitotic Signaling Network in Budding Yeast - Sreenivasan, Aparna (American Society for Microbiology, 1999)
In budding yeast, the Clb2 mitotic cyclin initiates a signaling network that negatively regulates polar bud growth during mitosis. This signaling network appears to require the function of a Clb2-binding protein called Nap1, the Cdc42 GTPase, and two protein kinases called Gin4 and Cla4. In this study, we demonstrate that the Elm1 kinase also plays a role in the control of bud growth during mitosis. Cells carrying a deletion of the ELM1 gene undergo a prolonged mitotic delay, fail to negatively regulate polar bud growth during mitosis, and show defects in septin organization. In addition, Elm1 is required in vivo for the proper regulation of both the Cla4 and Gin4 kinases and interacts genetically with Cla4, Gin4, and the mitotic cyclins. Previous studies have suggested that Elm1 may function to negatively regulate the Swe1 kinase. To further understand the functional relationship between Elm1 and Swe1, we have characterized the phenotype of Δelm1 Δswe1 cells. We found that Δelm1 Δswe1 cells are inviable at 37°C and that a large proportion of Δelm1 Δswe1 cells grown at 30°C contain multiple nuclei, suggesting severe defects in cytokinesis. In addition, we found that Elm1 is required for the normal hyperphosphorylation of Swe1 during mitosis. We propose a model in which the Elm1 kinase functions in a mitotic signaling network that controls events required for normal bud growth and cytokinesis, while the Swe1 kinase functions in a checkpoint pathway that delays nuclear division in response to defects in these events.